2002
DOI: 10.1007/s10158-002-0017-6
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against the presence of NMDA receptors at a central glutamatergic synapse in leeches

Abstract: The N-methyl- D-aspartate (NMDA) receptor, able to detect the coincidence of pre- and postsynaptic events, is considered to be the molecular analogue of associative learning. Associative learning is well known in leeches, particularly for reflexive shortening. The neuronal circuits underlying shortening have been documented and include neurons that release glutamate. Is this type of learning in leeches also mediated by NMDA receptors? The synapse between the P sensory neuron and the motoneuron-like AP cell was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Pilot experiments indicated that prolonged exposure to even micromolar concentrations of glycine nonspecifically facilitates synaptic transmission between leech neurons (data not shown), in agreement with published results using millimolar glycine concentrations (Wu, 2002). One hour after tetanic stimulation, S-cell EPSPs elicited by intracellular stimulation of the tetanized and nontetanized P-or T-cell inputs were separately retested (posttest) in a manner identical to the pretest measurements.…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…Pilot experiments indicated that prolonged exposure to even micromolar concentrations of glycine nonspecifically facilitates synaptic transmission between leech neurons (data not shown), in agreement with published results using millimolar glycine concentrations (Wu, 2002). One hour after tetanic stimulation, S-cell EPSPs elicited by intracellular stimulation of the tetanized and nontetanized P-or T-cell inputs were separately retested (posttest) in a manner identical to the pretest measurements.…”
Section: Methodssupporting
confidence: 86%
“…The glycine binding site appears to be conserved in invertebrate forms of the NMDAR (Brockie et al, 2001). It was necessary to apply glycine only during the tetanic stimulation because prolonged application nonspecifically increased P-cell synaptic transmission (Wu, 2002;B. D. Burrell, unpublished observations), possibly because application of sufficient amounts of glycine alone can induce LTP (Musleh et al, 1997;Lu et al, 2001;Man et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We would like to stress that the lingering controversy over the universality of the role of NMDA receptors as a key factor in learning and memory across different animal phyla, as well as over evolutionary aspects of functions for NMDA receptors (e.g., Wu, 2002;Rose et al, 2003) is primarily due to insufficient comparative data-especially data from basal metazoa (e.g., Pierobon et al, 2004;Scappaticci et al, 2004). Molecular and functional characterization of nonvertebrate homologs of these receptors would probably reveal novel regulatory mechanisms and pathways.…”
Section: Discussionmentioning
confidence: 99%
“…To date, NMDA receptor subunits have been cloned in arthropods (Ultsch et al 1993;Xia et al 2005;Zannat et al 2006), nematodes (Brockie et al 2001), and mollusks (Ha et al 2006), but there is no comparable evidence for the existence of these receptors in the leech or other annelids. Furthermore, several studies using pharmacological and immunohistochemical techniques have suggested that NMDA receptors are not present in the leech (James et al 1980;Mat Jais et al 1984;Brodfuehrer and Cohen 1990;Dorner et al 1990;Groome and Vaughan 1996;Thorogood et al 1999;Wu 2002;reviewed in Glantz and Pfeiffer-Linn 1992). This is in contrast to more recent pharmacological studies that indicate the presence of NMDA receptor-dependent plasticity in the leech (Burrell and Sahley 2004;Grey and Burrell 2008).…”
Section: Introductionmentioning
confidence: 96%